Prevalence of low-level viremia and related influencing factors among people living with HIV in China: a systematic review and meta-analysis - Zhang, Xinxin; Xu, Qianlei; Li, Chen; Zhang, Yue; Jin, Yantao; Li, Pengyu; Guo, Huijun (Frontiers in Public Health, 2025)
IntroductionThe promotion and application of ART have significantly reduced the mortality rate of AIDS patients in China, but the problem of LLV that follows cannot be ignored. LLV is closely associated with viral failure and increased all-cause mortality. Conducting a systematic study on the prevalence of LLV among PLWH in China and its influencing factors has significant clinical implications for the comprehensive management, effective prevention, and intervention of LLV in the future.MethodsStudies were included if research subjects were PLWH in China, with a duration of ART treatment of ≥6 months, the research types were cohort studies, case–control studies, and cross-sectional studies, the primary outcome indicator was LLV occurrence, as well as research findings were disseminated in Chinese or English. The systematic review was conducted using the R studio software.ResultsOur review included a total of 20 original studies, covering 225,687 HIV/AIDS patients, among which 45,265 were LLV. Our study showed that the overall prevalence rate of LLV among PLWH in China was 10.6% (95% CI: 6.8% ~ 16.1%). Further subgroup analysis revealed that Blip was higher than pLLV, the prevalence of LLV was the highest in the VL range of 50 ~ 199 cp/mL; there were no significant differences in the prevalence of LLV among different regions, type of study and ART regimens. The analysis of factors influencing LLV showed that poor ART adherence, baseline VL > 105 cp/mL, changing the treatment schemes, baseline CD4 < 350 cells/μL, PI-based regimen at initiation, age ≥50 years, and age of ART initiation ≥50 years were risk factors for LLV among PLWH, while homosexual transmission was a protective factor for LLV (p < 0.001).ConclusionThe prevalence of LLV among PLWH was moderate to low in China. Special attention should be paid to older population with PLWH who had poor ART adherence, high baseline VL, had changed the treatment schemes, had a low baseline CD4 level, had an PI-based regimen at initiation, started ART relatively late, and needed enhanced compliance management and drug resistance testing, as well as increased VL testing frequency to avoid adverse outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251047912, identifier (CRD420251047912).